PRESURB (2013)
The continuous technological evolution is one of the key factors to shorten the distance between the ideal and the real. Every day more construction companies conduct their activities with technological tools for budgeting, planning of construction activities, structural analysis, geotechnical analysis, among others. In case there are tools to budget, but these do not focus on the particularities of labor of each region. PRESURB By DMAC is created to meet the need of a tool for the realization of urbanites budgets in the city of Armenia, Quindío (Colombia).